Identification of coral fish species in the coral reef ecosystem in the coastal waters of Teluk Bakau Village, Bintan Regency Kepulauan Riau Province - Sari, Dini; Eddiwan, Eddiwan; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractIn the coastal water of TelukBakau village there is coral reef ecosystem that is inhabitby many coral fish species. Information on the types of coral fishes living in that area is limited. To understand the types of coral fishes in the coral reef ecosystem in that area, a study has been conducted in March-April 2019. Fish samplings were conducted once a weeks in 1 month. The fishes were captured using gill nets and bamboo traps. Fish samples were then identified. Results shown that the fish caught from the study area consistedof 2 orders, 13 families, 19 genera, and 28 species. The most common fish present during the study was the member of  Holocentridae and Lethrinidaefamilies. Keyword: Identification, Coral fish, Coral Reef Ecosystem, Teluk bakau, Bintan Regency